Persepsi Masyarakat terhadap Guru Anak Usia Dini Laki-Laki di Kecamatan Kawalu Kota Tasikmalaya: Community Perceptions of Male Early Childhood Teachers in Kawalu District, Tasikmalaya City - Rachman, Budi (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research is motivated by the low population of male early childhood school teachers which results in a low level of masculine roles for children while they are at school. Community assessment of male early childhood school teachers is an inseparable part of the high and low population of male early childhood school teachers in early childhood school units. In line with that, this research aims to look at the public's perception of male PAUD teachers in Kawalu District, Tasikmalaya City. By knowing the public's perception of male early childhood school teachers, it is hoped that this research can be a stimulus to increase the presence of male teachers in early childhood school units. The approach taken in this research is a quantitative approach with a descriptive survey method. The research tool used was a questionnaire with a Likert scale. The research data was processed using descriptive statistics. The results of the research show that the community has a positive perception of the presence of male early childhood school teachers, the community considers that male early childhood school teachers can act as masculine figurs and act as substitutes for fathers while their children are at school. The community also considers that male early childhood school teachers have quite challenges as professional early childhood school teachers. Ultimately, the community hopes that there will be an increase in the population of early childhood school teachers in early childhood school units, especially Kawalu District, Tasikmalaya City.